An investigation into interpersonal meanings in ‘the world is flat’ by thomas l. friedman and its vietnamese version ‘thế giới phắng’ by nguyễn hồng quang - Nguyễn,Thị Ngọc Mai (ĐHĐN., 2015)
This paper mainly focused on analyzing interpersonal meanings in ‘The World is Flat’ by Thomas L. Friedman on the basis of Hallidayan Functional Grammar, which has a significant effect on the view of traditional grammar in particular. ‘The World is Flat’ by Thomas L. Friedman is one of the most bestselling books in the world which reflects the trend of globalization. This is a favorite book of numerous people over the world which has been translated into various languages. This paper aimed at finding out the way the writer establishes relationship with the readers and expresses his attitude and opinion toward the 21st century’s issues of the world. In addition, this paper investigated the expressions of interpersonal meanings in the Vietnamese version “Thế Giới Phẳng” by Nguyễn Hồng Quang; then, it compared them with those used in the English version to explore the losses and gains in the Vietnamese version. The study was descriptive and quantitative. 544 English and Vietnamese clauses and short passages in the first and the second chapters of the two versions were used as the samples for the study. The findings indicated that in both English and Vietnamese versions, there were markers of the mood system, personal pronoun system and expressions of modality by which the interpersonal meanings were expressed. Implications for English or Vietnamese teaching and learning as second languages, for English-Vietnamese translation as well as for future research were discussed.